mRNA alternative polyadenylation (APA) in regulation of gene expression and diseases - Siyao Guo; Shuibin Lin (Genes and Diseases, 2023)
The mRNA polyadenylation plays essential function in regulation of mRNA metabolism. Mis-regulations of mRNA polyadenylation are frequently linked with aberrant gene expression and disease progression. Under the action of polyadenylate polymerase, poly(A) tail is synthesized after the polyadenylation signal (PAS) sites on the mRNAs. Alternative polyadenylation (APA) often occurs in mRNAs with multiple poly(A) sites, producing different 3′ ends for transcript variants, and therefore plays important functions in gene expression regulation. In this review, we first summarize the classical process of mRNA 3′-terminal formation and discuss the length control mechanisms of poly(A) in nucleus and cytoplasm. Then we review the research progress on alternative polyadenylation regulation and the APA site selection mechanism. Finally, we summarize the functional roles of APA in the regulation of gene expression and diseases including cancers.